Calculating the Impact of Trade on Aspects of Human Development in Central Europe Using Data Envelopment Analysis - Nowakowski, Joseph M. (Ekonomika, 2005)
Three equally weighted variables, material output life expectancy and literacy. comprise the widely used comprehensive measure of development known as the Human Development Index (HDI). Although the level of development for a society is constrained by its resource endowment traditional HDI calculations ignore this. Economic theory suggests that international trade leads to a more efficient use of resources and can contribute to economic development. This paper addresses the question of whether trade contributes only to material development, or whether it impacts life expectancy and literacy rates as well, taking into account differences in endowments and attitudes towards outcomes. The HDI values, with outcome flexibility. are calculated for a number of countries using data envelopment analysis, controlling for resource use. Then the impact of trade on different variables is considered. Economies in Central Europe or former Soviet republics, or both, are compared to the rest of the world to identify differences in performance and the influence, if any. of trade on performance. Relative to resource endowments, the subset of nations performs well relative to the rest of the world. Trade is seen to have varying influences in the two regions for certain performance variables.